TINJAUAN HUKUM TERHADAP PENDAFTARAN TANAH PERTAMA KALI DI KANTOR PERTANAHAN KABUPATEN KLATEN - SUKARNI, SUKARNI (Dinamika Hukum, 2015)
The purpose of this research is to review and to analyze the observation of law toward the first time registration of land in the district of Klaten and the obstacles and its settlement toward the first time land registration in order to implement legal certainty on property right of land in the district of Klaten. The background of the first time land registration is the societal expectations to provide letter of rights evidence, in form of certificate. Notion of certificate according to chapter 1 number 200 of Government Regulation No. 24 year 1997, is letter of rights evidence as it is mentioned in chapter 19 verse (2) letter c UUPA for right of land. Keyword : The First Time Registration